332 Antidepressant (AD) use in ovarian cancer patients (OC) in the past 26 years at the american university of beirut medical center (AUBMC). (18th September 2019) - Seoud, M; Abdallah, R; Dagher, C; Jaafar, I; Shamseddine, W; Jaafar, N
Abstract : Objectives: To assess the prevalence of antidepressant (AD) use and the factors affecting it in OC patients at AUBMC between the years 1992–2018. Methods: A Retrospective review of patients with OC stages I-IV cared for in AUBMC between 1992–2018, with focus on antidepressant use and the factors affecting it. Results: A total number of 330 subjects were enrolled in this study. Prevalence of antidepressant use is 11.8%. Anxiolytics were prescribed in 42.8% of cases. 20.3% of patients on anxiolytics were on AD as well (P-value<0.001). AD use was significantly higher among the advanced ovarian cancer patients (IIIC:37%, IV=39%) versus early stages (IA-IIIB=25%). 23.4% of diabetic patients versus 9.8% of non-diabetic patients were on AD (P-value=0.021), 26% of smokers versus 9% of non smokers (p=0.006), 28% of Dyslipidemics versus 8.7% of non-dyslipidemics (P-value<0.001), and 22.9% employed patients versus 11.3% of unemployed ones (Pvalue=0.057) were on AD. Antidepressant prescription was found to be significantly correlating with having dyslipidemia (OD=7.3, P-value<0.001), being on anxiolytics (OD=6.9, P-value<0.001), having an advanced FIGO stage(OD=3.7, P-value<0.001), and being employed (OD=3.66, P-value=0.02) (table 1 ). Conclusions: Depression among ovarian cancer patients is underestimated or not properly screened and treated. Advanced FIGO stage, being employed, dysplipidemic and anxiolytic are significant predictors for AD use.